Translation Challenges and Strategies Among EFL Students of English Language Education Study Program - Makmur Makarim Wartabone; Novriyanto Napu; Sri Widyarti Ali (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This study explores the translation challenges and strategies employed by EFL students in the English Language Education Study Program (ELESP) at Universitas Negeri Gorontalo. It adopts a quantitative descriptive design, collecting data from 38 fourth-semester students through a structured questionnaire adapted from Al-Sobh (2022). The instrument covered two key domains: ten items identifying various translation challenges and five items measuring the strategies students used to improve their translation competence. The findings reveal that students face considerable difficulties in several linguistic and cultural areas, particularly in interpreting pragmatic and semantic nuances, mastering grammatical structures, and bridging cultural gaps between the source and target languages. Despite these challenges, students actively implement a range of strategies, including intensive vocabulary learning, grammar-focused exercises, review of teacher feedback, and the application of translation skills through real-world texts. The study highlights the importance of both linguistic accuracy and cultural competence in translation training. These results provide valuable insights for enhancing translation pedagogy, particularly in EFL contexts, and offer recommendations for instructional practices to support students’ translation performance.